(untitled) - Đoàn, Thị Bích Điểm (Cần Thơ, 2010)
The purpose of this study is to introduce Webquest to teachers and students in a rural high school in Vinh long to examine their attitudes towards the implementation of webquest in English class.
Keywords: Education,Giáo dục,English language,Tiếng Anh; Computer network resources,Tài nguyên mạng máy tính,Study and teaching,Dạy và học